PENGARUH PENGELOLAAN PROGRAM ADIWIYATA TERHADAP BUDAYA SEKOLAH BERWAWASAN LINGKUNGAN DI SMA NEGERI KOTA PADANG - Fitri, Felia; Ningrum, Tia Ayu; Marika Setiawati; Widiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
An environmentally conscious school culture is crucial as it shapes the habits and character of the school community, fostering environmental care. However, several obstacles hinder the development of such a culture, including a lack of environmentally conscious habits, inconsistent enforcement of environmental regulations, environmental cleanup activities being limited to specific times, and insufficient environmental awareness and concern among teachers and the school community. Therefore, this study aims to determine the impact of adiwiyata program management on the environmentally conscious school culture in public high schools (SMA Negeri) in Padang City. The study employs a quantitative approach using a causal-associative method. The research population consists of teachers working in these schools, with 129 respondents selected via stratified proportional random sampling. Data were collected using validated and reliable questionnaires and subsequently analyzed using descriptive statistics, normality tests, linearity tests, simple linear regression, t-tests, and the coefficient of determination test, utilizing SPSS 26 for Windows software. The results indicate that the management of the adiwiyata program falls into the very good category, with a Respondent Achievement Level (TCR) of 92.12%, while the environmentally conscious school culture also falls into the very good category. Hypothesis testing reveals that adiwiyata program management significantly influences the environmentally conscious school culture, with a significance value of <0.001. The coefficient of determination (R²) of 0.536 indicates that adiwiyata program management contributes 53.6% to the environmentally conscious school culture. The study concludes that the management of the adiwiyata program has a positive and significant impact on the environmentally conscious school culture. In other words, the better the management of the adiwiyata program through planning, organizing, implementation, and evaluation the stronger the resulting environmentally conscious school culture. Schools are advised to maintain and enhance adiwiyata program management through continuous planning, organizing, implementation, and evaluation to further strengthen the environmentally conscious school culture.